Multiple Band Mobile Antenna for LTE, GSM, PCS, UMTS & IoT Applications - T P Madhav, B; Sai Dheeraj, G; S Raghavarapu, Sarvani (International Journal of Engineering and Technology, 2018)
A compact planar inverted folded antenna for LTE, GSM, PCS and UMTS applications is presented in this work. This paper provides the comprehensive study on the placement of mender line ground and its effect on the performance characteristics of the antenna operating bands. Results of intensive investigations by computer simulations are provided for antenna parameters like reflection coefficient (<-10 dB), VSWR (2:1), bandwidth, radiation patterns, field distributions and showcased the technical write-up in this paper. The proposed antenna offers an average gain of 3.4 dB and directivity of 3.8 dB at operating bands of 860 MHz, 960 MHz, 1800 MHz, 2100 MHz and 2700 MHz, which includes 4G and covers most of the applications bands for mobile communication. An impedance bandwidth of 32% at first resonant band (GSM), 26.6% at second resonant band (PCS), 26% at third resonant band (LTE) and 21% at fourth resonant frequency (UMTS) are obtained.Â Â